The future of off-pump coronary artery bypass grafting: a North American perspective - Yanagawa, Bobby; Nedadur, Rashmi; Puskas, John D. (Journal of Thoracic Disease; Vol 8, Supplement 10 (November 15, 2016): Journal of Thoracic Disease (Off-Pump Coronary Artery Bypass Grafting), 2016)
Off-pump coronary artery bypass graft (OPCAB) is currently performed routinely in a minority of specialized centers and in many more centers, utilized only when a porcelain aorta mandates a no-touch aortic technique. The OPCAB literature can be summarized as follows: (I) large-scale randomized trials in relatively low risk patients that include surgeons with a range of experience demonstrating no consistent beneficial differences in major cardiovascular and cerebrovascular outcomes but lower transfusion rates and shorter length of stay, tempered by some reports of higher rates of incomplete revascularization and lower rates of long term graft patency; (II) smaller randomized controlled trials (RCTs) from highly specialized programs demonstrating equivalent or superior outcomes with OPCAB and similar completeness of revascularization and graft patency; and (III) observational data from large databases demonstrating a consistent benefit of OPCAB, especially in higher-risk patient subsets. Our rationale for OPCAB remains that if complete and precise revascularization can be safely and routinely accomplished, then the patient should benefit by avoiding the morbidities that can be attributed to aortic cannulation/clamping, cardiopulmonary bypass (CPB), hemodilution, hypothermia and global myocardial ischemia/cardioplegia. We further believe that OPCAB procedures should emphasize the use of arterial grafts to optimize long term patency and minimize aortic manipulation to limit the risk of stroke. Moving forward, the off-pump surgical community and specialty societies must address the challenge of training surgeons and their teams to master this technically demanding procedure. Furthermore, OPCAB opens the door to minimally-invasive surgical revascularization via hybrid coronary revascularization (HCR). A large NIH-funded RCT is currently underway to determine whether hybrid revascularization can offer a superior alternative to multi-vessel percutaneous coronary intervention for patients with low SYNTAX score and proximal LAD disease.